PENERAPAN METODE PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN PPKN MATERI MERAJUT PERSATUAN ANTAR ELEMEN BANGSA PADA SISWA KELAS V SDN ORO-ORO OMBO KECAMATAN KARTOHARJO KOTA MADIUN SEMESTER 2 TAHUN PELAJARAN 2023 / 2024 - Indah Septiani; Sudarmiani; Novi A.Widianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the fact that education is one way to develop students' learning potential which includes cognitive, affective and psychomotor aspects. One of the subjects that suits this goal is PPKN. However, based on the results of observations, it shows that the PPKN learning achievement of class V students at SDN Oro-Oro Ombo, Kartoharjo District, Madiun City is low. This research aims to: 1) describe the PPKN learning process using the Problem Based Learning learning model in an effort to improve student learning achievement; 2) improve and describe student learning improvements using the Problem Based Learning learning model. This research includes classroom action research which was carried out in 2 cycles. The subjects of this research were 19 class V students. Data collection techniques in this research used observation, written tests and documentation. The data analysis carried out was descriptive-quantitative. The results of the research show that the application of the jigsaw type cooperative learning model can improve the learning achievement of class V students at SDN Oro-Oro Ombo, Kartoharjo District, Madiun City. Student learning achievement has increased from the initial condition of 58.3% with an average value of 60.50 to 76.50% with an average value of 69.83 in cycle I, and then increased to 86.98% with an average value of average